Gambaran Kadar Hemoglobin Dan Protein Urin Pada Ibu Hamil - Luh Putu Rinawati; Ni Putu Ditya Prabandari Dewi; Ni Putu Yulia Rahma Dewi; Ni Komang Omik Trianita Udiana; Ni Wayan Rika Kumara Dewi; Heri Setiyo Bekti (Meditory : The Journal of Medical Laboratory, 2022)
Backgrounds of hemoglobin is a metalloprotein in red blood cells that functions as an oxygen booster from the lungs to the rest of the body. To maintain hemoglobin levels in the body, especially in pregnant women, it is necessary to have adequate intake of nutrients, namely iron. If the intake of iron in pregnant women is less, it will increase the risk of anemia. Anemia is a condition or condition that causes low levels of hemoglobin (Hb). Albuminuria or proteinuria is a condition in which urine or urine contains an abnormal amount of albumin. Throughout pregnancy, pregnant women are usually advised to take a urine test. One of the focuses of the urine test is to determine urine protein levels in pregnant women. In pregnant women, there is a phase where urine protein levels increase, namely, lack of fluids, exposure to cold and extreme weather, new strenuous activities, and emotional stress also often causes urine protein levels in pregnant women to increase, and impaired kidney function. or urinary tract infection. The method we used in this research is descriptive research method to describe the levels of hemoglobin (Hb) and urine protein in pregnant women at the Ubud 1 Public Health Center, Gianyar-Bali. With the sampling technique using the probability sampling method, with a simple random sampling technique. The results of 41 respondents, that pregnant women who have normal Hb levels (≥ 11 g/dL) at Puskesmas Ubud 1 were found to be more than pregnant women who have low Hb levels ( 11 g/dL). And from the total sample, as well as 2 pregnant women from the urine protein level examination data were positive. The conclusion after averaging the Hb and urine protein levels of pregnant women at the ubud 1 health center that it can be said that the health condition of pregnant women is quite good, but there are still some respondents who show results that are not in accordance with normal limits, therefore it is important to maintain health and pattern healthy living.Keywords: hemoglobin, urine protein, pregnant women